Scaling Social Innovation Through Cross-Sector Social Partnerships : Driving Optimal Performance. - Pittz, Thomas G. (Emerald Publishing Limited, 2021)
This book is designed to illuminate the features of cross-sector partnerships that make them powerful vehicles to drive social change. Partnerships across market sectors, involving for-profit, non-profit, and government entities, work because they leverage the advantages of each type of organization to arrive at novel solutions to social problems.